Association of METS-IR with Pregnancy Outcomes in Euthyroid Women: A Retrospective Cohort Study - Lin, Jiaying; Xie, Qianwen; Guo, Zize; Lin, Xiang; Shen, Qi; Han, Mengyuan; Lin, Juan (Hormone and Metabolic Research, 2025)
The non-insulin-based metabolic score for insulin resistance (METS-IR) is a recently developed index aimed at being a practical and efficient alternative biomarker of insulin resistance (IR). This study aimed to investigate the association between METS-IR in euthyroid women in the first trimester of pregnancy and pregnancy outcomes. A total of 1810 participants who gave birth at Fujian Maternity and Child Health Hospital from November 2018 to November 2019 were included in this study. Thyroid function, fasting blood glucose (FPG) levels, lipid profiles, and anthropometric parameters were collected during the first trimester of pregnancy. METS-IR was calculated by FPG, total triglyceride, high-density lipoprotein cholesterol, and body mass index. Pregnancy outcomes were collected. There were 75 (4.1%) cases of macrosomia and 433 (23.9%) cases of gestational diabetes mellitus (GDM). Participants were divided into four groups based on METS-IR, with a median and interquartile range of METS-IR levels of 23.91 (22.83, 24.67), 26.53 (25.88, 27.17), 29.13 (28.47, 30.00), and 33.59 (32.10, 36.21), respectively. The higher METS-IR quartile was significantly associated with macrosomia and GDM (p<0.05). The risk of macrosomia and GDM increased with the increased METS-IR levels when METS-IR was a continuous variable, particularly METS-IR levels reaching 27.84 and higher (overall p<0.05). We found no correlation between METS-IR and low birth weight, cesarean section, and preterm delivery (p>0.05). Increasing METS-IR in euthyroid women in the first trimester of pregnancy may predict macrosomia and GDM.
Keywords: METS-IR; macrosomia; GDM; pregnancy outcomes; insulin resistance